ANALISIS TOTAL QUALITY MANAGEMENT DAN OPEN GOVERNMENT TERHADAP PRODUKTIVITAS KERJA - Oki Irawan; Sumardi , (Fakultas Ekonomi dan Bisnis Islam, 2021)
Total Quality Management becomes the strategy of companies to attract consumer satisfaction in a long period of time. Similarly, Open Government is an effort to increase public trust. Both of these things are what a company needs to increase public trust including Uhamka as an entity engaged in education services. This study aims to analyze the influence of Total Quality Management and Open Government on the productivity of employee performance UHAMKA. This study using the purposive sampling method and testing conducted with multiple regression analysis, hypothesis test, coefficient of determination analysis, and classical assumption test. The test results stated that partially Total Quality Management did not have a significant influence on employee productivity. While Open Government partial has a significant influence on employee productivity.